Sterilization of extracted human teeth: A comparative analysis - Simarpreet V. Sandhu; Rajiv Tiwari; RamanPreet K. Bhullar; Himanta Bansal; Rajat Bhandari; Tushaar Kakkar; Ridhima Bhusri (Journal of Oral Biology and Craniofacial Research)
Background: Extracted human teeth are regularly used for practice and educational purposes in dental institutions at undergraduate and postgraduate levels. Different materials and methods are used for sterilizing extracted teeth to avoid infection from them. Aims: The present study was done to determine the efficacy of some frequently used methods for disinfection/sterilization of extracted human teeth. Materials and methods: A total of 120 intact, non-carious teeth extracted due to periodontal or orthodontic purpose were divided randomly into 8 groups consisting of 15 teeth in each group. Agents used for sterilization included 10% formalin, 0.1% thymol in distilled water, 5.25% sodium hypochlorite, 2% glutaraldehyde, 3% hydrogen peroxide, boiled in water (100 °C), autoclave (121 °C, 15 lbs psi), normal saline. Samples were collected with the help of inoculating loop and then streaked over the surface of Mc-Conkey agar medium and Blood agar medium. The media were then incubated at 37 °C for 24 h. No visible growth in the culture medium was considered as the method of effective sterilization. Results: 10% formalin, autoclaving, 5.25% sodium hypochlorite could be efficiently used for sterilization and disinfection of extracted human teeth. Conclusion: Extracted teeth should be handled with extreme care as these are potential source of infection and need to be disinfected before they are used in the laboratories.